2012
DOI: 10.1063/1.4724206
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting fluctuations and anomalous phonon renormalization much above superconducting transition temperature in Ca4Al2O5.7Fe2As2

Abstract: Raman studies on Ca 4 Al 2 O 5.7 Fe 2 As 2 superconductor in the temperature range of 5 K to 300 K, covering the superconducting transition temperature T c ~ 28.3 K, reveal that the Raman mode at ~ 230 cm -1 shows a sharp jump in frequency by ~ 2 % and linewidth increases by ~ 175 % at T o ~ 60 K. Below T o, anomalous softening of the mode frequency and a large decrease by ~ 10 cm -1 in the linewidth is observed. These precursor effects at T 0 ( ~ 2T c ) are attributed to significant superconducting fluctuatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Raman spectroscopic technique has been proved to be very useful for probing 2D as well bulk systems and their various aspects such as layer stacking geometry, strain effect, thermal properties, defects, number of layers, and so on [5,7,[12][13][14][15][16][17][18][19][20]. Several authors have employed temperaturedependent Raman scattering to estimate thermal properties like TEC and thermal conductivity via monitoring the behaviour of the phonon modes as a function of temperature [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopic technique has been proved to be very useful for probing 2D as well bulk systems and their various aspects such as layer stacking geometry, strain effect, thermal properties, defects, number of layers, and so on [5,7,[12][13][14][15][16][17][18][19][20]. Several authors have employed temperaturedependent Raman scattering to estimate thermal properties like TEC and thermal conductivity via monitoring the behaviour of the phonon modes as a function of temperature [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, let us not jump to conclusions. Owing to the presence of SC fluctuations, a lot of intriguing physics occurs in superconductors above T c [18][19][20] , and this is of great interest specially in low-dimensional 21,22 and high T c superconductors 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Towards understanding the elementary excitations in FeBS, a few temperature-dependent Raman studies have been reported on these iron-based superconductors "1111" [22][23], "122" [24][25][26][27][28][29][30][31], "11" [32][33][34], "42622" [35] systems. The phonon anomalies observed in these systems have been attributed to mechanism such as strong spin-phonon coupling, opening of the spin density wave (SDW) gap, first-order structural phase transition and change of the charge distribution within the Fe-As plane.…”
Section: Introductionmentioning
confidence: 99%